In Sacco Degradability Kinetics of Cumbu Napier (COBN-5) Fodder at Two Different Stages of Harvest - M, Madesh; K, Raja Kishore; D, Srinivas Kumar; A, Anitha (Indian Journal of Animal Nutrition, 2020)
In the present study, Cumbu Napier (COBN-5) fodder was evaluated for nutrient degradability in sacco using three rumen fistulated Murrah buffalo bulls (380 Â± 9.36 kg BW) fed ad libitum COBN-5 fodder at two different stages (40 and 45 days) of harvest. The average in sacco disappearance values (%) of DM, CP, NDF and ADF were 80.49, 91.97, 74.11 and 73.79 after 72 h incubation in the rumen, respectively. The readily soluble fraction (a) for DM, CP, NDF and ADF was higher in the fodder harvested at 40 days, whereas, higher insoluble but degradable fraction (b) for DM, CP, NDF and ADF was reported in the fodder harvested at 45 days. Further, potentially degradable fraction, PD (a+b) for DM and CP was lower, and for NDF and ADF was higher in the fodder harvested at 40 days. The effective degradability (%) of DM, CP, NDF and ADF was higher in the fodder harvested at 40 days than in 45 days. Results indicated that COBN-5 fodder can be effectively included in the rations of live stock starting harvested at 40 days for effective utilization.